Does the provision of community health services offset the effects of poverty and low maternal educational attainment on childhood mortality? An analysis of the equity effect of the Navrongo experiment in Northern Ghana - Ayaga A. Bawah; James F. Phillips; Patrick O. Asuming; Elizabeth F. Jackson; Paul Walega; Edmund W. Kanmiki; Mallory C. Sheff; Abraham Oduro (Elsevier, 2019)
The Government of Ghana has instituted a National Poverty Reduction Program with an initiative known as the Community-based Health Planning and Services (CHPS) as its core health development strategy. CHPS was derived from a plausibility trial of the Navrongo Health Research Centre testing four contrasting primary health care strategies: i) Training unpaid volunteers to promote health in communities, ii) placing nurses in communities with training and supplies for treating childhood illnesses, iii) combining the nurse and volunteer approaches, and iv) sustaining a comparison condition whereby clinic services were provided without community resident workers. This paper presents an age-conditional proportional hazard analysis of the long term impact of community health worker exposure among 94,599 children who were ever under age five over the January 1, 1995 to December 2010 period, adjusting for age conditional effects of shifts in exposure type as CHPS was scaled up in Navrongo project area over the 1995-2000 period. Results show that children whose parents are uneducated and relatively poor experience significantly higher mortality risks than children of the educated and less poor. Conditional hazard regression models assess the impact of CHPS on health equity by estimating the interaction of equity indicators with household exposure to CHPS service operations, adjusting for age conditional exposure to original Community Health and Family Planning Project (CHFP) service strategies as scale-up progressed. The association of mortality risk among children with uneducated and relatively impoverished mothers is offset by exposure to community health nursing services. If exposure is limited to volunteer-provided services alone, survival benefits arise only among children of relatively advantaged households. Findings lend support to policies that promote the CHPS nurse approach to community-based services as a core health component of poverty reduction programs. Keywords: Community health, Childhood mortality, Maternal education, Equity, Ghana